Complicações do cateter venoso central em pacientes submetidos ao transplante de células tronco hematopoéticas de um serviço especializado - Barretta, Lidiane Miotto (2014)
Introduction: Hematopoietic Stem Cell Transplantation is a long, complex, and high-cost process, which demands an appropriate hospital infrastructure and a qualified multidisciplinary team. The major cause of morbidity and mortality in transplanted patients is infection. The insertion of a semi-implantable, long-term central venous indwelling catheter poses a risk of complications, such as obstruction, fracture or breakage, migration, infection, and death. Objectives: The aims of the present study were to characterize the patients undergoing hematopoietic stem cell transplantation and to identify complications related to the central venous catheter and to describe the associated complications between the variables (sex, age, diagnosis, kind of transplantation, type of catheter, site of catheter insertion, and the length of time with the catheter. Methods: This was a retrospective, quantitative study conducted at a teaching hospital in inland of São Paulo State. Transplanted patients’ names were retrieved from the medical records and from the nursing forms. Files were reviewed retrospectively. The study involved the analysis of 188 patients’ files from 2007 to 2011. Association between variables was compared using the Chi-square test and the univariate analysis. Continuous variables were compared using Student’s t-test. Independent variables were analyzed using the Mann-Whitney test, Anova and the Kruskal-Wallis test. P = 0.05 was considered statistically significant. We used the correspondence analysis and multivariate technique to analyze the categorical variables. Results: Most patients were married man with age ranging from 40 to 60 years. They worked in general services and came from the cities of São Paulo and Mato Grosso States. They were patients from the Unified Health System (SUS) diagnosed with Hodgkin's lymphoma, multiple myeloma and non-Hodgkin lymphoma undergoing autologous transplantation. The major complications were constipation, diarrhea, urinary tract infection, respiratory infection and graft versus host disease. However, most patients survived the transplant and were discharged. The Hickman catheter was the most used catheter, with a mean length of time with the catheter of 47.6 days. The fever/bacteremia complication was more incident in young males with non-Hodgkin lymphoma and autologous transplantation, who remained with the catheter for a long period in the subclavian vein. Conclusion: Characterizing the patients’ profile, identifying the diagnosis, complications of treatment, the current situation of the post transplanted patients, provide grants to nursing professionals in search of a safer practice with actions related to prevention. Complications of catheter and its relation to age, gender, medical diagnosis, type of transplant, catheter model, mean residence time and insertion site should be analyzed considering the conditioning protocol, which directly affects the occurrence of complications and injury Related catheter.